Variabilidade espaço-temporal do fitoplâncton ao longo de um gradiente salino em um estuário tropical de macromaré na margem equatorial brasileira - CAVALCANTI, Lisana Furtado (2018)
The structure of the phytoplankton community (composition, distribution and biomass) and environmental conditions were characterized along the salinity gradient in a tropical macrotidal estuary - Paciência river estuary. The Paciência river estuary is located on the Brazilian Equatorial Margin, playing an important role in contributing to the water supply, agriculture, fishing and aquaculture activities. It is characterized by the wide mangroves occurrence and in natura sewage discharge. For the seasonal and spatial analysis of environmental and biological variables, quarterly surveys were performed at thirteen sampling points during the rainy period (April 2017), transitional period (June 2017) and dry period (October 2017). The ecological patterns of phytoplankton were explored by SIMPER and Cluster Analysis and tested by Redundancy Analysis. The community composition included a total of 171 identified taxa, divided in seven divisions with Bacillariophyta as the most representative division (128 taxa). The phytoplankton structure in the Paciência river estuary showed typical characteristics of tropical estuaries marked by a salinity gradient, governed by rainfall and river discharge. From this, three scenarios related to seasonality and salinity gradient were identified: river zone (1 to 3 sampling points; S ≤ 15 g Kg-1), mixing zone (4 to 7 sampling points; 15 > S < 30 g Kg-1) and coastal zone (8 to 13 sampling points; S ≥ 30 g Kg-1), controlled by seasonal periods. During the rainy and transitional seasons, it was observed a spatial gradient of salinity, characterized by the gradual increase in phytoplankton abundance and biomass from the inner zones (salinity <20 g.Kg-1) towards the coastal zone (salinity> 30 g.Kg-1), with the highest nutrient concentrations in the river zone. During the dry season, the homogeneous gradient of salinity (salinity> 30 g.Kg-1) favored the occurrence of Thalassiosira rotula blooms, which were responsible for the high phytoplankton biomass and lower nutrient concentrations. In both periods, diatoms were the dominant group due to their euryhaline nature, which provides high abundance in estuarine ecosystems. Hence, this work contributes to the understanding of the phytoplankton dynamics, reinforcing the importance of phytoplankton monitoring for the identification of ecological changes in the Paciência river estuary.